A Rare Presentation of Orbital Roof Blow-out Fracture with Intact Vision - Yadav, Arbindra Kumar; Ray, Manohar Kumar; Magar, Birat Thapa; Thapa, Dinesh Kumar; Karki, Karuna Tamrakar; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2019)
The orbital blowout fracture is most common in its inferior and medial wall; however we are presenting here a rare case of superior orbital wall blowout fracture with intact vision. This is a presentation of a 55 year-old right handed gentleman following road traffic accident had left orbital injury causing orbital roof fracture. Despite of such a huge injury there was no deterioration of his vision and his movements of the eye balls were also absolutely preserved.